Grain size effects and weakest link theory in 3D crystal plasticity simulations of polycrystals - Gélébart, Lionel (Comptes Rendus. Physique, 2021)
The weakest link theory, sometimes proposed to analyze size effects on the plastic behaviour of single crystals, is introduced in 3D numerical simulations of polycrystals. The approach relies on a random distribution of sources in space and strength associated to a crystal plasticity law with constant per layer Critical Resolved Shear Stresses (CRSS). It is able to reproduce: (1) the grain size dependence of the yield stress given by the Hall–Petch law, (2) intense slip band localization patterns as often observed at the grains surface, especially pronounced in quenched or irradiated metals, but difficult to reproduce by numerical simulation.